Fluorescence probe study of the interaction between acrylic acid-co-ethyl methacrylate copolymers and sodium dodecylsulfate - de Oliveira Tiera, V. A.; Tiera, M. J.; Neumann, M. G. (Marcel Dekker Inc, 2001)
The interaction between sodium dodecylsulfate (SDS) and acrylic acid (AA)-ethyl methacrylate (EMA) copolymers has been investigated using steady state fluorescence and conductimetric measurements to assess the effect of the polymer composition on the aggregation process. Micropolarity studies using the ratio between the emission intensities of the vibronic bands of pyrene (I-1/I-3) and the shift of the fluorescence emission of pyrene-3-carboxaldehyde show, that the interaction of SDS with AA-EMA copolymers occurs at surfactant concentrations smaller than that observed for the pure surfactant in water and depends on the copolymer composition. The increase of ethyl methacrylate in the copolymers lowers the critical aggregation concentration (CAC) due to the larger hydrophobic character of the polymer backbone. The formation of aggregates on the macromolecule is induced mainly, by hydrophobic interactions, but the process is also influenced by the ionic strength due to the counter-ions of the polyelectrolyte.